2014
DOI: 10.1186/s12998-014-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractor interaction and treatment equivalence in a pilot randomized controlled trial: an observational analysis of clinical encounter video-recordings

Abstract: BackgroundChiropractic care is a complex health intervention composed of both treatment effects and non-specific, or placebo, effects. While doctor-patient interactions are a component of the non-specific effects of chiropractic, these effects are not evaluated in most clinical trials. This study aimed to: 1) develop an instrument to assess practitioner-patient interactions; 2) determine the equivalence of a chiropractor’s verbal interactions and treatment delivery for participants allocated to active or sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…The fact that clinicians were not blinded to the treatment assignment, even though instructed to behave the same towards all patients, may still have resulted in different behaviors and procedures within each of the two treatment arms. Previous research have shown that that clinician behavior may change and result in a systematic bias with regards to the interaction with the patient in an un-blinded procedure [71, 72]. Although the treatment assignments was known to the clinicians, they were completely naïve to the psychological status and subgroup assignment as the method for the subgroup analysis was not presented or discussed prior to the study.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that clinicians were not blinded to the treatment assignment, even though instructed to behave the same towards all patients, may still have resulted in different behaviors and procedures within each of the two treatment arms. Previous research have shown that that clinician behavior may change and result in a systematic bias with regards to the interaction with the patient in an un-blinded procedure [71, 72]. Although the treatment assignments was known to the clinicians, they were completely naïve to the psychological status and subgroup assignment as the method for the subgroup analysis was not presented or discussed prior to the study.…”
Section: Discussionmentioning
confidence: 99%